(untitled) (American Journal of Islam and Society, 2001)
This important new addition to the growing body of literature on nationalism, religion, and religious nationalism is the product of a conference on "Religion and Nationalism in Europe and Asia", held in 1995 at the University of Amsterdam. Princeton University Press is in general hesitant when it comes to publishing edited volumes; it has done well to make an exception for this one. While many edited collections, particularly those that grow out of conferences, are at best of inconsistent quality and at worst entirely lacking in coherence, van der Veer and Lehmann’s Nation and Religion is striking both for the high quality of each individual essay it contains and for the depth and force of the overall argument that emerges from the volume as a whole. That argument is an important and provocative one: that modernity, contrary both to modernity’s own depiction of itself and to much historiography of the modem period, is not characterized by the eradication of religion’s relevance to politics. On the contrary, the varied chapters in this book show religion to be a near-ubiquitous feature of the political landscape and discourse of the so-called "First" and "Third" Worlds alike. The volume is made up of ten chapters that together deal with the relationship between religion and politics in the Netherlands, Great Britain, India, and Japan. The fullest coverage is given to India, which is approached from different perspectives in four different chapters: van der Veer’s "The Mod State: Religion, Nation, and Empire in Victorian Britain and British India", Susan Bayly’s "Race in Britain and India", Partha Chatterjee’s "On Religious and Linguistic Nationalisms: The Second Partition of Bengal", and Barbara Metcalf’s "Nationalism, Modernity, and Muslim Identity in India before 1947". This particular focus on India is a reflection both of van der Veer’s own specific interests and training and of the fact that India - both British imperial and modem national - lends itself particularly well to analysis concerned with the interplay between religion, politics, and modem nationalisms. The British dimension of van der Veer and Bayly’s chapters is expanded by Hugh McLeod in his contribution on "Protestantism and British National Identity, 1815-1945". The volume also includes two chapters on the Netherlands (Peter van Rooden’s "History, the Nation, and Religion: The Transformations of the Dutch Religious Past", and Frans Groot’s "Papists and Beggars: National Festivals and Nation Building in the Netherlands during the Nineteenth Century") and one on Japan (Harry Harmtunian’s "Memory, Mouming, and National Morality: Yasukuni Shrine and the Reunion of State and Religion in Postwar Japan"). Despite the diversity of time and place reflected in the volume, the essays read remarkably well together as a whole - the result of a clearly-conceived and carefully edited project. Additional coherence comes from the ...